EGFR: Tale of the C-terminal tail - Gajiwala, Ketan S (Blackwell Publishing Ltd, 2013)
The carboxy terminal tail of epidermal growth factor receptor (EGFR) plays a critical role in the regulation of the enzyme activity of the kinase. There is a good structural model for the mechanism by which the C-terminal tail proximal to the kinase domain contributes to the negative regulation of the activity. Its conformation in the active state, conversely, has remained elusive due to its dynamic nature. A recently published structure of EGFR kinase domain shows the conformation of the proximal C-terminal tail in the active kinase. Analysis of this conformational state of the C-terminal tail is presented, and some of the mutagenesis data is revisited. © 2013 The Protein Society